2015
DOI: 10.3390/pharmaceutics7040413
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Synthesis and Biomedical Applications of Nanocomposite Hydrogels

Abstract: Hydrogels sensitive to electric current are usually made of polyelectrolytes and undergo erosion, swelling, de-swelling or bending in the presence of an applied electric field. The electrical conductivity of many polymeric materials used for the fabrication of biomedical devices is not high enough to achieve an effective modulation of the functional properties, and thus, the incorporation of conducting materials (e.g., carbon nanotubes and nanographene oxide) was proposed as a valuable approach to overcome thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 156 publications
0
18
0
Order By: Relevance
“…Burst release of the therapeutics is often encountered in many polymer and hydrogel based formulations [10,27]. While the photothermal triggered release of insulin was demonstrated by Matteini [10], no details about loading/release capacity as well as on the insulin activity after photo-triggered release were given so far, crucial parameters when it comes to consider therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Burst release of the therapeutics is often encountered in many polymer and hydrogel based formulations [10,27]. While the photothermal triggered release of insulin was demonstrated by Matteini [10], no details about loading/release capacity as well as on the insulin activity after photo-triggered release were given so far, crucial parameters when it comes to consider therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the successful application of graphene oxide and carbon nanotubes in drug delivery for cancer therapy [ 131 ]; however, only a few studies describe their role in the delivery of polyphenols. For instance, a promising modality describes the polyphenol-induced reduction of graphene oxide, resulting in the bond formation between polyphenols and graphene oxide [ 132 ].…”
Section: Polyphenol-loaded Polymeric Nanotherapeutics For Cancer Tmentioning
confidence: 99%
“…All these functionalizations are exohedral derivatizations. A special case is the endohedral functionalization of CNTs, i.e., filling of the tubes with atoms or small molecules [6,32] One of the most common functionalization techniques is the oxidative treatment of CNTs by liquid-phase or gas-phase oxidation, introducing carboxylic (−COOH) groups and some other oxygen-bearing functionalities such as hydroxyl, carbonyl, ester, and nitro groups into the tubes. In this process, CNTs are treated by strong acids, such as refluxing in a mixture of sulfuric acid and nitric acid [9,10], "piranha" solution (sulfuric acid-hydrogen peroxide) [11], boiling in nitric acid [12], or treating with oxidative gases, such as ozone [6,33].…”
Section: Functionalization Of Cntsmentioning
confidence: 99%